The Role of Perceived Value and Satisfaction in Shaping Customer Citizenship Behavior: Evidence from Turkey - Karahan, Mehmet Ozan (International Review of Management and Marketing, 2024)
Tourism and hospitality companies are now providing more opportunities for collaborative production and value utilization. This isn’t just to encourage customers to revisit and repurchase, but also to capitalize on customer citizenship behaviors, such as feedback, advocacy, helping other customers, and showing tolerance in situations where services might be less satisfactory in the future. Hence, this study investigates the effect of perceived value and satisfaction on customer citizenship behavior within the hospitality and tourism contexts in Turkey. The study also examines the mediating role of satisfaction on sub-dimensions of customer citizenship behavior. Data were collected from guests in Turkey who had stayed there most recently within the previous 12 months. Using purposive sampling technique, an online survey was conducted to collect data. Of the 612 accepted responses that met all the criteria, were analyzed using structural equation modeling (SEM) through AMOS 25 software. The results showed that perceived value has significant and strong influences on satisfaction, feedback, tolerance, and advocacy as sub-dimensions of customer citizenship behavior. Satisfaction has significant and strong influences on feedback and help as sub-dimensions of customer citizenship behavior. Finally, satisfaction mediates between perceived value and feedback and help.